Performance of the ALICE VZERO system - Abbas, E.; Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agnello, M.; Agocs, A. G.; Agostinelli, A.; Ahammed, Z.; Ahmad, N.; et al. (IOP PUBLISHING LTD, 2013)
ALICE is an LHC experiment devoted to the study of strongly interacting matter in proton-proton, proton-nucleus and nucleus-nucleus collisions at ultra-relativistic energies. The ALICE VZERO system, made of two scintillator arrays at asymmetric positions, one on each side of the interaction point, plays a central role in ALICE. In addition to its core function as a trigger source, the VZERO system is used to monitor LHC beam conditions, to reject beam-induced backgrounds and to measure basic physics quantities such as luminosity, particle multiplicity, centrality and event plane direction in nucleus-nucleus collisions. After describing the VZERO system, this publication presents its performance over more than four years of operation at the LHC.
Keywords: Large detector-systems performance; Trigger detectors; Large detector systems for particle and astroparticle physics; Heavy-ion detectors; Instruments & Instrumentation